Metal–organic framework based antibiotic release and antimicrobial response: an overview. Issue 44 (20th October 2020) - Kaur, Navpreet; Tiwari, Pranav; Kapoor, Kshipra S.; Saini, Anoop Kumar; Sharma, Vinay; Mobin, Shaikh M.
Abstract : MOF and MOF based heterostructures for antibacterial applications. Abstract : Metal–organic frameworks (MOFs) are porous crystalline materials in which multidentate organic ligands and transition metal cations are linked via coordination bonds. The porosity of MOFs enables them to be used as drug carriers. Moreover, the presence of multiple coordination bonds makes them a desirable candidate for sustainable release of drugs which is a prerequisite for the treatment of many chronic and virulent intracellular infections by bacteria. These properties of MOFs have been extensively studied and utilized in various antibacterial studies where MOFs were used as antibacterial drug carriers or they themselves showed antibacterial activity or in composite form with many other available antimicrobial nanomaterials. This review focuses on the recent advances in MOFs and MOF composites for antibacterial drug delivery in various biological systems.